The complete mitochondrial genome of Arctium lappa (Campanulales, Asteraceae). Issue 2 (2nd April 2020) - Zhang, Da-Chuan; Xing, Yan-Ping; Xu, Liang; Zhao, Rong; Yang, Yan-Yun; Zhang, Ting-Ting; Li, Sheng-Nan; Kang, Ting-Guo
Abstract: Complete mitogenome sequence of an important medicinal plant, Arctium lappa, was determined for the first time. The entire circular genome is 312, 598 bp in length (GenBank accession number SRX7565441), with 45.43% GC contents. The genome has 131genes, including 33 known protein-coding genes (PCGs), 25 transfer RNAs (tRNAs), and 6 ribosomal RNAs (rRNAs). The phylogenetic trees are built based on 32 plants, using the maximum-likelihood method. The data will provide certain help to subsequent botany for classifying plants